Learning from intersectoral initiatives to respond to the needs of refugees, asylum seekers, and migrants without status in the context of COVID-19 in Quebec and Ontario: a qualitative multiple case study protocol - Lara Gautier; Erica Di Ruggiero; Carly Jackson; Naïma Bentayeb; Marie-Jeanne Blain; Fariha Chowdhury; Serigne Touba Mbacké Gueye; Muzhgan Haydary; Lara Maillet; Laila Mahmoudi; Shinjini Mondal; Armel Ouffouet Bessiranthy; et al. (BMC, 2023)
Abstract Background Refugees, asylum seekers, and migrants without status experience precarious living and working conditions that disproportionately expose them to coronavirus disease 2019 (COVID-19). In the two most populous Canadian provinces (Quebec and Ontario), to reduce the vulnerability factors experienced by the most marginalized migrants, the public and community sectors engage in joint coordination efforts called intersectoral collaboration. This collaboration ensures holistic care provisioning, inclusive of psychosocial support, assistance to address food security, and educational and employment assistance. This research project explores how community and public sectors collaborated on intersectoral initiatives during the COVID-19 pandemic to support refugees, asylum seekers, and migrants without status in the cities of Montreal, Sherbrooke, and Toronto, and generates lessons for a sustainable response to the heterogeneous needs of these migrants. Methods This theory-informed participatory research is co-created with socioculturally diverse research partners (refugees, asylum seekers and migrants without status, employees of community organizations, and employees of public organizations). We will utilize Mirzoev and Kane's framework on health systems' responsiveness to guide the four phases of a qualitative multiple case study (a case being an intersectoral initiative). These phases will include (1) building an inventory of intersectoral initiatives developed during the pandemic, (2) organizing a deliberative workshop with representatives of the study population, community, and public sector respondents to select and validate the intersectoral initiatives, (3) interviews (n = 80) with community and public sector frontline workers and managers, municipal/regional/provincial policymakers, and employees of philanthropic foundations, and (4) focus groups (n = 80) with refugees, asylum seekers, and migrants without status. Qualitative data will be analyzed using thematic analysis. The findings will be used to develop discussion forums to spur cross-learning among service providers. Discussion This research will highlight the experiences of community and public organizations in their ability to offer responsive services for refugees, asylum seekers, and migrants without status in the context of a pandemic. We will draw lessons learnt from the promising practices developed in the context of COVID-19, to improve services beyond times of crisis. Lastly, we will reflect upon our participatory approach-particularly in relation to the engagement of refugees and asylum seekers in the governance of our research.